Kolaborasi Pemerintah Dan Masyarakat Dalam Pengembangan Kawasan Wisata Pantai Air Manis Di Kota Padang - Salwatul Aisy; Fuji Syaulend Utami; Eliza Mohga Elhakim; Boni Saputra (CV. ITTC INDONESIA, 2026)
Air Manis Beach combines coastal scenery, the Malin Kundang heritage narrative, local businesses, and public tourism services. Its development therefore requires coordination among the Padang City Government, Padang Sejahtera Mandiri Regional Public Company, tourism awareness groups, local residents, and business actors. This study analyzes the pattern, outcomes, success factors, and constraints of collaborative governance in the destination. The research used a qualitative descriptive design through a pure literature review. Searches were conducted in Google Scholar, GARUDA, Crossref, and official journal portals. Sixty-seven records were identified, and 20 peer-reviewed journal articles published between 1995 and 2025 were included after duplicate removal, title and abstract screening, and full-text assessment. Data were extracted into a literature matrix and analyzed thematically using collaborative governance and community-based tourism frameworks. The findings show that government and the regional company dominate policy, infrastructure, ticketing, and operational coordination, while communities contribute to visitor services, cleanliness, parking, local businesses, promotion, and cultural interpretation. Collaboration has produced economic opportunities and service improvements, but it remains operational-participatory rather than fully institutionalized. Success is supported by local economic incentives, role complementarity, leadership, community attachment, and capacity building. Major constraints include the absence of a permanent multi-stakeholder forum, unequal decision-making power, inconsistent safety and amenity standards, weak waste management, limited heritage protection, and inadequate joint monitoring. The study proposes a permanent collaborative forum, shared indicators, transparent benefit distribution, integrated safety management, and periodic evaluation.